Pengembangan Literasi Dongeng Lima Gunung (LIDOMAGU) Berbasis Digital Online di Masa Pandemi Covid-19 dalam Rangka Mendukung MBKM - Nugraheni, Molas Warsi; Baihaqi, Imam (Kajian Bahasa dan Sastra (KABASTRA), 2021)
This study aims to develop LIDOMAGU online digital learning media and find out the implementation of LIDOMAGU in supporting MBKM in the PBSI Untidar. This research uses mixed-method research with research and development (R & D) design and qualitative data analysis. The research phase uses the Romiszowski (1996) design with the name ADDIE development model with the steps (1) analysis (2) design (3) development (4) implementation and (5) evaluation. The product is developed using an application maker application, namely appsgeyser which can be downloaded via an android device at the address https://appsgeyser.com and a display design using the Canva application. The product is validated with 3 validation tests, namely content validation, learning design validation and media validation. The average score obtained is 88 which is in the valid category.